Market design for the procurement of reactive power: The current state in Germany - Anna Pechan; Marius Buchmann (Constructor University Bremen, Bremen Energy Research (BER), 2023)
The market-based procurement of system services for network operators is gaining momentum in the current debate about the future market design in the energy sector. Since current sources of reactive power are primarily fossil-fuel power plants which will not be available in a carbon neutral energy system, reactive power will be sources from distributed assets in the electricity networks. The German regulator has proposed new rules for reactive power procurement, which are based on three pillars: The technical connection agreements, fully integrated network components owned by the network operators and market-based procurement. While this approach is primarily aiming at the reactive power demand on the transmission grid level, assets from the medium voltage grid can participate in this process as well. We evaluate this approach from an economic perspective and conclude that while such a three-pillar system can secure an effective provision of reactive power, the efficiency heavily depends on the regulatory system and that it provides the correct incentives for the network operator.
Keywords: D47; L51; L94; 330; reactive power; electricity; network; market design